Structural break unit-root: an empirical study of Malaysian equity markets - Chin, Wen Cheong; Zaidi Isa (Universiti Kebangsaan Malaysia, 2009)
This research investigated the unit-root tests using nonparametric sequences-reversals (S-R), Phillip-Perron (PP) tests and parametric Augmented Dickey-Fuller (ADF) test for the Malaysian equity indices. Under the considerations of drift and structural break, it was found that during the restructuring period after the Asian financial crisis, most of the indices provided evidences against the unit-root tests. These results are somewhat contrasted with the conventional unit-root tests that ignored the impact of structural changes. In addition, the S-R tests were found to have little power to identify the deviations from the unit-root even after the inclusion of structural break.